2021
DOI: 10.1007/s11606-021-06808-3
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Spirituality and Religion in Physician and Trainee Wellness

Abstract: Burnout in medicine is a substantial problem with adverse consequences for both physicians and the patients who they treat. In our efforts to combat burnout, we must consider every tool at our disposal, since a complex problem requires a multifaceted approach. Recognizing that many physicians derive meaning from spirituality and religion, attempts to improve physician and trainee wellness should acknowledge the importance of religion and spirituality for self-care more than has heretofore been the case.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 21 publications
1
6
0
Order By: Relevance
“…4 Spirituality has also been associated with a decreased risk for burnout among physicians and trainees. 5 A similar correlation has been observed among medical students, with higher levels of spirituality being associated with lower levels of burnout and psychological distress, with spirituality possibly acting as a protective factor. 6 Few studies have also found an inverse correlation between substance abuse and spirituality in college and medical students, with higher levels of spirituality correlating with lower rates of substance abuse as well as rates of binge drinking.…”
Section: Introductionsupporting
confidence: 58%
“…4 Spirituality has also been associated with a decreased risk for burnout among physicians and trainees. 5 A similar correlation has been observed among medical students, with higher levels of spirituality being associated with lower levels of burnout and psychological distress, with spirituality possibly acting as a protective factor. 6 Few studies have also found an inverse correlation between substance abuse and spirituality in college and medical students, with higher levels of spirituality correlating with lower rates of substance abuse as well as rates of binge drinking.…”
Section: Introductionsupporting
confidence: 58%
“… 22 , 23 Prior studies have shown the benefits of self-care practices (such as mindfulness, yoga, and spirituality) on reducing healthcare worker burnout, stress, and anxiety. 24 , 25 , 26 , 27 , 28 , 29 , 30 Our survey indicated that most infection preventionists find importance in both individual self-care practices and spirituality for promoting well-being. As such, organizational level changes which accommodate opportunities for healthcare workers to engage in self-care practices (even if briefly) throughout the course of work shifts may help to promote well-being, reduce burnout, and improve patient safety.…”
Section: Discussionmentioning
confidence: 86%
“…While religion is important to many physicians, workplace discrimination based on religious identity remains understudied, 25,26 and studies of US Muslim physicians are rare. [27][28][29] Examining physician experiences with religious discrimination and institutional responses to the religious needs of physicians can further illuminate how diversity, equity, and inclusion (DEI) can be advanced in the health care workplace.…”
Section: Introductionmentioning
confidence: 99%